Synergistic effect of GO/ZnO loading on the performance of cellulose acetate/chitosan blended reverse osmosis membranes for NOM rejection - Rizwana Shami; Aneela Sabir; Sadia Sagar Iqbal; Nafisa Gull; Rubab Zohra; Shahzad Maqsood Khan (Heliyon, 2023)
Declining freshwater resources along with their pollution are threatening the life existence on earth. To meet the freshwater demand, one of the most appropriate and possible ways which has been adopted all over the world is to reuse wastewater by removing its impurities. Among many water pollutants, natural organic matter (NOM) is found to be responsible as major precursor for the formation of other pollutants. Removal of NOM from wastewater is being done by using membrane filtration systems incorporated with certain nanofillers to increase membranes efficiency and permeability. In this study, novel nanocomposite reverse osmosis (RO) membranes were prepared using cellulose acetate and chitosan in N,N-Dimethyl formamide. Graphene oxide (GO) nanosheets and zinc oxide (ZnO) in different concentration were loaded to modify the membranes for tuning their RO performance. The confirmation of the functional groups is demonstrated by Fourier transform infrared spectroscopy which revealed the specific peaks indicating the formation of the nano-composite membranes. The surface morphology was studied by scanning electronic microscopy which shows a gradual transformation of the membrane surface from voids-free to macro-voids filled surface up to threshold concentration of GO and ZnO. The thermal properties of GO based membranes were analyzed using thermogravimetric analysis and differential scanning calorimetry. The uniform interaction of the GO and ZnO with polymers induced the remarkable thermal properties of the synthesized membranes. Permeate flux and contact angle measurements were considered to estimate their water content (96%) capacity and NOM rejection (96%) using 0.1 ppm humic acid solution. The permeate flux, NOM rejection and the water content changed directly with GO and inversely with ZnO wt% in the membranes up to GO5 (GO:0.14: ZnO:0.03) whereas the contact angle exhibited the inverse relationship with GO and ZnO concentration in casting solution of the synthesized membranes. Hence it can be concluded that prepared RO membranes are suitable for NOM rejection and recommended for water treatment.